Pemodelan Pemilihan Moda Rute Medan–Binjai Antara Kereta Api dan Bus dengan Metode Stated Preference - Zagoto, Indra Markeshwan; Sitindaon, Charles; Sitohang, Oloan (Fakultas Teknik Universitas Katolik Santo Thomas, 2018)
The objective of this research is to construct a user mode choice model between BRT Mebidang and Sri Lelawangsa railway line, and further to test the sensitivity of trip user choice toward certain change in attributes value. Data were collected using stated preference survey, and analysed using logit biner model. Based on user responses, it was found that 50.96% trip purpose is related to family/social matter, while the main reason to travel using both modes is convenience. The tility function of Mebidang bus is given as follow: UBM-KA = 7.256 - 0.565X1 - 0.031X2 + 0.101X3 - 0.071X4 + 0.088X5 where X1 is cost, X2 is time, X3 is headway, X4 is accesstime, dan X5 is service quality. The model shows that cost, time, and access time negatively affect Mebidang bus utility thus will lower the probability of user choosing bus over rail. In terms of sensitivity, access time and service quality are considered more sensitive in affecting the probability of choosing bus.